Enhancing Students' Argumentation and Reflective Judgment in Biology learning through LMS based on Socio-Scientific Issues - Putra, Edysyah; Vebrina, Dinda (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to develop a biology learning device based on socio-scientific issues (SSI) assisted by a Learning Management System (LMS). It employs the ADDIE development model, which consists of the stages of Analysis, including needs analysis, initial and final analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of one material expert, one media expert, and 36 high school students. Data were collected using assessment instruments and questionnaires to obtain reviews and recommendations from experts on the developed biology learning device. Based on data analysis from the assessment results of two validators, the average score (PRS) of biology learning devices in the aspect of biological study information is 80 (high), the aspect of learning organization is 82 (high), the aspect of web/LMS operational presentation is 82 (high), and the aspect of biological study language is 84 (high), thus making the overall average of 82.29 (high). From the PRS results obtained, it can be concluded that the LMS biology learning device based on SSI to improve the argumentation and reflective judgment skills of high school students meets the validity aspect and can be implemented in high school students' biology learning.